The Culinary Sector MSME Survival Strategy in Effort to Restore Populist Economy Based on the Creative Industry during the Covid-19 Pandemic - Mangasi Sinurat; Lilinesia Lilinesia; M Subhan; Amsyal Simanjuntak (Department of Management, Universitas Malikussaleh, Aceh Utara, Indonesia, 2021)
This study aims to identify and analyze strategies to improve the economic recovery of MSMEs in the culinary sector during the Covid-19 pandemic and when the new normal era was implemented due to the impact of the Covid19 pandemic. The research method used is descriptive qualitative method.The results obtained from this study indicate that there is a need for quick, precise and real steps from the government and business actors to overcome the losses that have occurred due to the pandemic as well as updating and evaluating the business cycle following the current situation. happens so that the business can continue to survive and grow.